2008
DOI: 10.1152/ajpregu.00084.2008
|View full text |Cite
|
Sign up to set email alerts
|

Simulated microgravity alters rat mesenteric artery vasoconstrictor dynamics through an intracellular Ca2+release mechanism

Abstract: Colleran PN, Behnke BJ, Wilkerson MK, Donato AJ, Delp MD. Simulated microgravity alters rat mesenteric artery vasoconstrictor dynamics through an intracellular Ca 2ϩ release mechanism. Am J Physiol Regul Integr Comp Physiol 294: R1577-R1585, 2008. First published March 19, 2008 doi:10.1152/ajpregu.00084.2008.-Previous work has shown that orthostatic hypotension associated with cardiovascular deconditioning results from inadequate peripheral vasoconstriction. We used the hindlimb-unloaded (HU) rat in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 56 publications
5
27
2
Order By: Relevance
“…The increase in RyR1 expression and function in VSMC of HU rats fits with the different effects measured previously and provides a new insight complementary to the increase in Ltype Ca 2+ current density and membrane VDCC α 1C subunit expression described in cerebral VSMC after HU [51]. RyR1 appears to be a major target of vascular adaptation to HU and the regulation of its expression depends on the effects of HU on the intravascular blood loading [7,12,28]. If the cellular sensor of gravity is not yet described, the modulation of RyR1 expression was described before not only in VSMC but also in skeletal muscle [3].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The increase in RyR1 expression and function in VSMC of HU rats fits with the different effects measured previously and provides a new insight complementary to the increase in Ltype Ca 2+ current density and membrane VDCC α 1C subunit expression described in cerebral VSMC after HU [51]. RyR1 appears to be a major target of vascular adaptation to HU and the regulation of its expression depends on the effects of HU on the intravascular blood loading [7,12,28]. If the cellular sensor of gravity is not yet described, the modulation of RyR1 expression was described before not only in VSMC but also in skeletal muscle [3].…”
Section: Discussionsupporting
confidence: 81%
“…The vascular adaptation to μG likely involves a response of factors known to regulate blood pressure, including: (1) control of plasma volume [37]; (2) modulation of baro-and cardiopulmonary reflexes inducing the decrease of cardiac function [19]; and finally (3) adaptation of intrinsic properties of vascular endothelial and smooth muscle cells (VSMC). We have focused our study on this last factor and used the hindlimb unloaded (HU) rat model as it simulates the biological effects of μG; especially, modulations of vascular reactivity were described in this model [7,28,39,53]. Vascular reactivity and tone are regulated by complex Ca 2+ signals.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there is a report that 14-day hindlimb unloading decreased the level of intracellular Ca 2+ in rat small mesenteric VSMCs by reducing the function of ryanodine-sensitive Ca 2+ releases associated with the downregulation of RyR2 mRNA and protein expression [18]. We also reported that 28-day simulated microgravity down-regulated the Ca L channels in rat small mesenteric VSMCs [17].…”
Section: Introductioncontrasting
confidence: 58%
“…In humans, impairments of macro-and microcirculation are also involved in this downregulation (1). On rodent models, studies were carried out and showed that simulated weightlessness has negative effects on structural (13) and functional properties (8,14) of vasculature. Another part of this downregulation is an alteration of equilibrium system (40).…”
Section: Why Countermeasure Had No Effect On Orthostatic Responsementioning
confidence: 99%